A biodanza na percepção das mulheres: um encontro com a espiritualidade e a saúde - Ferreira, Maria Aparecida Porte (2019)
The study aimed to investigate the importance of biodanza as a practice of care and its influence on the spirituality and the perception of women in the biodanza group. The research was carried out with seven women, who participate in the biodanza group, in the Equilibrio do Ser / CPICS - Municipal Health Secretariat - João Pessoa / PB. The research was based on the following questions: What is the impact of biodanza on women's lives? How can biodanza influence women's health and spirituality? The theoretical dialogue focused on relating concepts and meanings about biodiversity and spirituality, as well as addressing gender issues and caring for women's health. It was recorded that biodanza presents a specific theoreticalmethodological and experiential model that is anchored in the Biocentric Principle. The five lines of life (vitality, sexuality, creativity, affectivity and transcendence) have an integrative effect that acts on the boby at all levels: emotional, neurological, endocrine and immunological, modifying lifestyle, awakening self-consciousness and creates new motivations to live. The disconnection and disassociation between body / soul / spirit / nature / sacred / profane, etc. can lead to pathology, as alert Rolando Toro. Spirituality is understood as an essential component for health and is expressed in individual search, giving new meaning to people's lives. In biodanza, transcendence is the healthy expression of spirituality, and it is impossible to conceive of spirituality without vitality, the vital energy. Thus, the body, matter becomes an essential channeling component that allows connection, expression and encounter with spirituality. It, this is a qualitative, research of phenomenological nature with a hermeneutical approach. It was performed through a questionnaire application and guided interviews with women participatins of the biodanza group. The research highlighted dialogues Rolando Toro (1991), Boff (1999), Lelloup (2003), Frankl (2008), Jung (1990), Eliade (2011), Bourdieux (2004), Koenig (2012), Rohr (2012), Creswell (2014), Masini (2010), Maturana and Varela (1990), Capra (1997), Possebon (2018), Possebon (2017) among others that we sought to engage in dialogue. According to the research it can be understood that biodanza plays a fundamental role in the life the woman who practices it. The recognition of the feminine self is the first step for the woman to awaken from deep sleep and to find strength, balance and harmony within her.